An in-service address; the foundations of education - Richard A. Brosio (Educational Considerations, 1976)
Education is a field, and an institutional reality, in which fierce arguments are raging. There simply Is no consensus regarding what good education is in America in the last quarter of the twentieth century. There are no experts and no consensus, but we are still committed to wrestling with the most difficult questions concerning the school and the society.